Diseño de objetos de aprendizaje visualizados mediante realidad aumentada como apoyo al proceso de enseñanza - aprendizaje de la asignatura de estudios sociales dirigido a los estudiantes de décimo año de educación básica en la unidad educativa “Amelia Gallegos Díaz” de la ciudad de Riobamba, durante el período lectivo 2015-2016 - Chávez Achache, Liseth Adriana (2016)
In the bibliographic research done on the Ministry of Education website could not be found multimedia didactic materials that serve as support for teachers in the Social Studies subject teaching process, which presents mostly theoretical content. Nowadays education should be more meaningful and motivating for student, such that the theory is more bearable for him. A technological design was used to develop this research work, field research and application level, the students from tenth year of Basic Education in the Unidad Educativa “Amelia Gallegos Díaz” during the academic year 2015-2016 were taken as an object of study, so it was obtained the probability sample. In order to demonstrate the significance of the project was designed Learning Objects using the “AODDEI Methodology”, with were displayed by mobile devices, with augmented reality application AURASMA. The evaluation scale of Learning Objects was used, which was proposal by Hernandez (2013), taking into account the criteria established by the ISO/IEC 9126: functionality, efficiency, usability, reliability, maintainability and portability. It is carried out the analysis and interpretation of data and as result is obtained by students with a 95.16% favorable to level of satisfaction regarding the use of learning objects and teacher qualification of 42.3 points in quality begin located in the very good range. After obtaining these results, it is recommended to integrate ICT in the classroom, creating new teaching strategies that support teachers in the teaching process and encourage the student to achieve meaningful learning.